Spray-Induced Gene Silencing (SIGS) as a Tool for the Management of Pine Pitch Canker Forest Disease - Bocos-Asenjo, Irene Teresa; Amin, Huma; Mosquera, Sandra; Díez-Hermano, Sergio; Ginésy, Mireille; Diez, Julio Javier; Niño-Sánchez, Jonatan (Plant disease, 2025)
Global change is exacerbating the prevalence of plant diseases caused by pathogenic fungi in forests worldwide. The conventional use of chemical fungicides, which is commonplace in agricultural settings, is not sanctioned for application in forest ecosystems, so novel control strategies are imperative. Spray-induced gene silencing (SIGS) is a promising approach that can modulate the expression of target genes in eukaryotes in response to double-stranded RNA (dsRNA) present in the environment that triggers the RNA interference mechanism. SIGS exhibited notable success in reducing virulence when deployed against some crop fungal pathogens, such as , , and , among others. However, there is a conspicuous dearth of studies evaluating the applicability of SIGS for managing forest pathogens. This research aimed to determine whether SIGS could be used to control , a widely impactful forest pathogen that causes pine pitch canker disease. Through a bacterial synthesis, we produced dsRNA molecules to target fungal essential genes involved in vesicle trafficking ( , , and ), signal transduction ( , , , and ), and cell wall biogenesis ( , , , and ) metabolic pathways. We confirmed that is able to uptake externally applied dsRNA, triggering an inhibition of the pathogen's virulence. Furthermore, this study pioneers the demonstration that recurrent applications of dsRNAs in SIGS are more effective in protecting plants than single applications. Therefore, SIGS emerges as an effective and sustainable approach for managing plant pathogens, showcasing its efficacy in controlling a globally significant forest pathogen subject to quarantine measures.